Peranaan Perusahaan Ekspor Ikan Hias dan Sumbangannya Bagi Perekonomian di DKI Jakarta - Ayub V Hanafiah (Buletin Ekonomi Perikanan, 1996)
Since 1991, the Indonesia ornamental fish exported has shown raising and about 70% of its was exported by the Province of DKI Jakarta. The export companies play an important role and contribute for the development of the ornamental fish business and economi activities in Indonesia, especially OKI Jakarta.The objective of this research is to study the economic impacts generated from exporting ornamental fish, by export companies in DKI Jakarta. Research was conducted by using the secondary data from statistical report, sinetific journals, and various publications; Time pattern series data period of 1989-1995 was utilized to analyze trend pattern of exported ornamental fish from OKI Jakarta. The results of study showed that the roles of exported companies increase depending on increasing activities of aquaculture and fishing ornamental fish. Activities of ornamental fish export companies have a positive impact on employment, income of fish farmers and fisherman and also contribute generate government income from retributions and taxes.